The Impact of CSR Contributions on Sustainable Development: A Quantitative Analysis of Bank Syariah Indonesia’s Medan Branch (2023–2024) - Hasanah, Aulia Nurul; Harmain, Hendra; Syakir, Ahmad (Journal of Social Work and Science Education, 2025)
This research aims to analyze the influence of the Corporate Social Responsibility (CSR) contributions of Bank Syariah Indonesia Medan Branch A.H. Nasution on sustainable development during the 2023–2024 period. Using a quantitative approach, data were collected from 220 beneficiaries of the CSR program in the fields of education, economy, health, social, and environment. The analysis was conducted using multiple linear regression and Structural Equation Modeling (SEM) through SmartPLS software. The results indicate that all dimensions of CSR significantly affect sustainable development, with community participation as a mediating variable that strengthens this relationship. The highest sustainability index is achieved in the education and health sectors. This study emphasizes the importance of CSR design based on local needs, transparency, and continuous evaluation. These findings contribute theoretically to the development of a measurable CSR model, as well as practical recommendations for sharia financial institutions in supporting the Sustainable Development Goals (SDGs) agenda.